(3GNJUGQ GdOjHGL GdePgH dGHf aQMhf aj WHbGJ GdeGdcjIs - (3CHh ESMGb EHQgje Hf gdGd GdSLdeGSis; (3GHf gdGd , EHQGgje Hf gdGd Hf Ydj GdUfgGLj GdZdGej GdSLdeGSj, CHh GSMGb,J (B903 (3g` s
(3ChdgG (B:s
(3ef cJGH GdOjHGL GdePgH aj eYQaI abgGA GdePgH ddEeGe GdbGVi CHj ESMGb EHQGgje QMeg Gddg JYGdi GdEeGe eGdc QMeg Gddg s
(3BNQgG (B:s
(3hef cJGH GdPjd hGdJcedI hef ahGFO TjNfG GdEeGe GdMGaX Yaja GdOjf GdeWQi hZjQg ef GdKbGJ s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B124s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B21 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs